Optimization of Electrode Material Composition from Activated Carbon, MWCNT & Graphene to Enhance Performance of Supercapacitor - Rustamaji, Heri; Prakoso, Tirto; Devianto, Hary; Widiatmoko, Pramujo (Journal of Engineering and Technological Sciences, 2022)
The supercapacitor has gotten a lot of attention as a high-performance energy storage device because of its high power density, good energy density, long life cycle, and extensive application in various electronic applications. To effectively assess its performance, the electrode material composition was optimized with a blend of activated carbon (AC), multiwall carbon nanotube (MWCNT), and graphene (GR). The synergistic effect of AC, CNT, and GR supports the usage of AC/MWCNT/GR as a viable supercapacitor electrode. Furthermore, the surrounding MWCNT enhances AC and GR electronic conductivity, while AC efficiently suppresses GR re-stacking sheets and aggregates MWCNT particles. For supercapacitor electrodes, the optimal composite mixtures of AC, MWCNT, and GR were 71.7%, 20%, and 8.3% wt, respectively. Meanwhile, an outstanding capacitance value of 33.5 F g-1 in 6 M KOH electrolyte was obtained at 2 mV s-1.